Photonics-based treatments: Mechanisms and applications in oral infectious diseases - Huang, Shan; Qi, Manlin; Chen, Yingxue (Frontiers in Microbiology, 2023)
Abstract: Infectious diseases remain a serious global challenge threatening human health. Oral infectious diseases, a major neglected global problem, not only affect people’s lifestyles, but also have intimate association with systemic diseases. Antibiotic therapy is a common treatment. However, the emergence of new resistance problems hindered and enhanced the complication of treatment. Currently, antimicrobial photodynamic therapy (aPDT) has long been the topic of intense interest due to the advantage of minimally invasive, low toxicity, and high selectivity. aPDT is also becoming increasingly popular and applied in treating oral diseases such as tooth caries, pulpitis, periodontal diseases, peri-implantitis, oral candidiasis, etc. Another phototherapy, photothermal therapy (PTT) also plays an important role in resisting resistant bacteria and biofilms infections. In this mini review, we summarized the latest advances in photonics-based treatments of oral infectious diseases. The first part is focus on photonics-based antibacterial strategies and mechanism. The second part presents applications for photonics-based treatments of oral infectious diseases. The last part discusses present problems in current materials and future perspectives.